Lowered obesity indicator cutoff points more effectively predict 5-year incidence of hypertension in premenopausal women. (28th August 2018) - Chu, Fu-Ling; Jeng, Chii
Abstract: Objective: To compare proposed new cutoff points for four obesity indicators—waist-to-height ratio (WHtR), waist circumference (WC), waist-to-hip ratio (WHR) and body mass index (BMI)—with their current cutoff points to determine which are better standards predicting 5-year incidence of hypertension (HT) and diabetes mellitus (DM) among premenopausal women. Design: Data were obtained from the 2002 and 2007 Survey on the Prevalence of HT, Hyperglycemia and Hyperlipidemia in Taiwan conducted by the Ministry of Health and Welfare, Taiwan. Premenopausal women were grouped based on the proposed cutoff points versus reference cutoff points for obesity indicators. Participant: A total of 1466 premenopausal women aged between 20 and 57 years old were recruited. Main outcome measure: Five-year incidence of HT and DM. Results: Our new obesity indicator cutoff points—WHtR 0.49, WC 74.7 cm, WHR 0.79 and BMI 22.3 kg/m 2 —were better predictors for 5-year HT incidence in premenopausal women compared with those of current standards, but were not significantly different for DM. Among the four obesity indicators, WHtR and WC were optimal for their 5-year predictive ability for HT and DM in premenopausal women. Conclusions: To avoid too many cutoff points for practitioners to adopt and memorize, the proposed new cutoff points were recommended preferentially to prevent the incidence of HT and DM in premenopausal women.